Some Questions about "Armas de la Antigua Iberia" - de Francisco Heredero, Ana (Gerión. Revista de Historia Antigua, 2012)
This paper is a critical analysis of F. Quesada’s work Armas de la Antigua Iberia. De Tartesos a Numancia, recently published. Even though we value the importance informative and as overall work, we find in this book some assertions regarding the weaponry, tactics and conception of war in the pre-Roman Iberian Peninsula that must be qualified.
Keywords: Pre-Romanweapons; Iberia; Celtiberia; Tartessos; War; Warrior clubs.